2020
DOI: 10.2183/pjab.96.002
|View full text |Cite
|
Sign up to set email alerts
|

Forward genetic approach for behavioral neuroscience using animal models

Abstract: Forward genetics is a powerful approach to understand the molecular basis of animal behaviors. Fruit flies were the first animal to which this genetic approach was applied systematically and have provided major discoveries on behaviors including sexual, learning, circadian, and sleep-like behaviors. The development of different classes of model organism such as nematodes, zebrafish, and mice has enabled genetic research to be conducted using more-suitable organisms. The unprecedented success of forward genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 252 publications
(162 reference statements)
0
6
0
Order By: Relevance
“…Genetic diversity is the primary driver for differences in molecular rhythms, which ultimately regulate physiological and behavioral rhythms. Previous studies have shown that genetic variants or mutations in canonical circadian genes lead to marked changes in circadian rhythm phenotypes across many different organisms 3 , 4 , 30 . Single base mutations in Per2 31 or Clock 32 genes altered period of behavioral rhythms in mice 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic diversity is the primary driver for differences in molecular rhythms, which ultimately regulate physiological and behavioral rhythms. Previous studies have shown that genetic variants or mutations in canonical circadian genes lead to marked changes in circadian rhythm phenotypes across many different organisms 3 , 4 , 30 . Single base mutations in Per2 31 or Clock 32 genes altered period of behavioral rhythms in mice 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to identify new genes or variants that modulate the amplitude, phase, or period of the clock have heavily relied on mice to leverage their genetic diversity and availability of genetics tools 3 , 4 . While these efforts have been valuable, many of these studies have used common inbred mouse strains or conventional inbred crosses that are constrained by their narrow genetic and phenotypic range.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these deletion in mice causes embryonic lethality and developmental abnormalities, making these mutants unsuitable for studying sleep/wakefulness. Please consult our previous review on this topic for more details [21].…”
Section: Forward Genetic Studies In Randomly Mutagenized Animalsmentioning
confidence: 99%
“…Another case of surviving without sleep came from fruit fly studies. In Drosophila melanogaster , natural inactivity states are commonly defined as “sleep” ( Funato, 2020 ). Drosophila locomotor inactivity lasting at least 5 min shares behavioral hallmarks of sleep in humans such as specific posture, increased arousal threshold, reversibility, and homeostatic regulation, and when following rest (“sleep”) deprivation, flies showed an increase in consecutive “sleep” ( Hendricks et al, 2000 ; Shaw et al, 2000 ; Funato, 2020 ).…”
Section: Life Without Sleepmentioning
confidence: 99%
“…In Drosophila melanogaster , natural inactivity states are commonly defined as “sleep” ( Funato, 2020 ). Drosophila locomotor inactivity lasting at least 5 min shares behavioral hallmarks of sleep in humans such as specific posture, increased arousal threshold, reversibility, and homeostatic regulation, and when following rest (“sleep”) deprivation, flies showed an increase in consecutive “sleep” ( Hendricks et al, 2000 ; Shaw et al, 2000 ; Funato, 2020 ). Some studies have reported that sleep deprivation in flies could be lethal or decrease lifespan ( Shaw et al, 2002 ; Ly et al, 2018 ; Vaccaro et al, 2020 ).…”
Section: Life Without Sleepmentioning
confidence: 99%